Волкодав: роман / М. Семенова - Семенова Мария Васильевна (АСТ, 2007)
Экземпляры: аб (20200206) / Инвентарный номер: 54864 / Цена: 70.00 / Сис.шифр: Р2 / Авт.знак: С 30 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6